Non-integrability and the KAM theorem - Bensa, Jaš (Matrika, 2019)
A general solution to Hamiltonian dynamical systems is in most of the cases not known. The KAM theorem qualitatively describes the orbits of a family of solvable systems after a small perturbation is applied. It helps us to understand the dynamics of complex systems and predict some characteristics of the motion.
Keywords: dinamični sistemi; dynamical systems; integrability; integrabilnost; KAM izrek; KAM theorem; ne-integrabilnost; non-integrability; perturbacije; perturbations